GeoSPARQL query support for scientific raster array data. (February 2022) - Almobydeen, Shahed Bassam; Viqueira, José R.R.; Lama, Manuel
Abstract: This paper presents the design of a GeoSPARQL query processing solution for scientific raster array data, called GeoLD. The solution enables the implementation of SPARQL endpoints on top of OGC standard Web Coverage Processing Services (WCPS). Thus, the semantic querying of scientific raster data is supported without the need of specific raster array functions in the language. To achieve this, first Coverage to RDF mapping solutions were defined, based on the well-known W3C standard mappings for relational data. Next, the SPARQL algebra is extended with a new operator that delegates part of the GeoSPARQL query in WCPS services. Query optimization replaces those parts of the SPARQL query plan that may be delegated to a WCPS service by instances of such new WCPS operator. A first prototype has been implemented by extending the ARQ SPARQL query engine of Apache Jena. Petascope was used as the WCPS implementation on top of the Rasdaman raster array database. An initial evaluation with real meteorological data shows, as it was initially expected, that the approach outperforms an existing reference relational database based GeoSPARQL implementation. Highlights: Efficient support for GeoSPARQL queries on top of raster coverages. Definition of raster coverage to RDF mapping approaches. Federated vector–raster geospatial queries enabled with SPARQL. Raster data access enabled without additional specific operators beyond GeoSPARQL.